PANTI SOSIAL TRESNA WERDHA DI BANJARBARU - Fadhliatun Najibah; Dahliani Dahliani (ULM Press, 2024)
Panti Sosial Tresna Werdha (PSTW) in Banjarbaru is an alternative residence intended for neglected elderly. The neglected elderly are categorized into two types, including economically neglected and socially neglected. This affects both physical and non-physical needs. To meet their needs, Tresna Werdha social institutions provide housing and various facilities that support elderly activities. Apart from physical needs, non-physical needs are the most important thing for the elderly. To be able to interpret the non-physical aspects for the elderly, it is necessary to review using the Behavioral Architecture method. This method aims to review space elements which will then be eaten with an understanding of home by aspects of Order, identification and dialectic processes. This is still a basis to be applied to the analysis. So the need for the theory of the hierarchy of basic human needs (maslow) to translate the analysis into a concrete form (architecture) in the form of physical needs physiological.needs, safety.needs, belongingness.needs, esteem.needs and.self.actualization. The concept refers to the five aspects of Maslow's theory which is contained in the concept of function and site in the design of the Panti Sosial Tresna Werdha (PSTW) in Banjarbaru.